(untitled) (Scientiae Studia, 2008)
The central question addressed is: How should scientific research be conducted so as to ensure that nature is respected, its regenerative powers not further undermined and wherever possible restored, and the well being of everyone everywhere enhanced? Then, after pointing to the importance of methodological pluralism for an acceptable answer, and the obstacles posed by identifying science with technoscience that are reinforced by what I call 'the commercial-scientific ethos', two additional questions are considered: How might research, conducted in this way, have impact on - and depend on - strengthening democratic values and practices? And, what is thereby implied for the responsibilities of scientists today? Since appropriate social conditions are not in place for exercising the responsibilities that are identified, exercising them also involves scientists participating in efforts to establish them. The paper concludes by suggesting that establishing these conditions would involve a complex dialectic that involves at least eight elements.